As dramaturgias que dançam em cenas brasileiras e seus fazeres artísticos - Amorim, Joisy Palmira de (2023)
This research aims to critically reflect on the dramaturgical construction in contemporary dance, through the discussions that emerge from the relationship between the choreographer and his artistic work, in the universe of the structuring and composition of the show. In this context, the concepts of choreography and dramaturgy will be investigated, as well as their interconnection in the process of artistic making in contemporary dance. Two choreographers were chosen: Suely Machado (First Act Dance Group, Belo Horizonte / MG) and Alejandro Ahmed (Scene 11 Group, from Florianópolis/SC), who have performed in the Brazilian scene for over 20 years. Given the complexity of the thematic approached and the subjective aspects present in each particular story, we chose a dialogical and dialectical methodological way, researching the subjects in their singularities and in different contexts. In the end it is intended to identify a possible methodology that supports and sustains the dramaturgical and choreographic practice in contemporary dance as scientific research in Performing Arts.